The Internal influences of consumers’ online shopping of wooden products during COVID-19 pandemic - Badrul Hisyam, Puteri Farahin Shameera; Harun, Zubaidah; Zainudin, Norzalina; Ismail, Mohd Hasmadi (Human Resource Management Academic Research Society, 2022)
Online shopping is the present future trend of shopping. However, the usage of online shopping platforms seems to be a new norm not just because of technological advances but due to the pandemic COVID-19. This study was focused more on wooden products since there were a limited number of studies about these products, especially in Malaysia. There are four items of internal influences that were considered: ease of use, experience, time management, and lifestyle that will influence online shopping of wooden products by Malaysians. The study aims to identify the most influential internal factors influencing the online shopping intention of wooden products during the pandemic outbreak by Malaysians. The survey was executed between June to July 2021 during the Movement Control Order (MCO) of COVID-19. The data was collected online using a form questionnaire distributed via social media such as WhatsApp, Facebook and Instagram, which covers 464 respondents. Later the data were analysed by multi-linear regression technique using SPSS ver. 26. The results of the study found that lifestyle is the most influencing factor towards online shopping, with a standardized coefficient (?) of 0.410. This is followed by experiences with 0.139, time management with 0.132 and ease of use with 0.076. The researcher concluded that changes in lifestyle into new norms, especially during Movement Control Order (MCO), lead the changes in consumers’ behaviour in purchasing goods. Besides, the online marketplace puts all the information at their fingertips, which facilitates consumers to purchase online.